2013
DOI: 10.1007/s00436-013-3457-5
|View full text |Cite
|
Sign up to set email alerts
|

Using mitochondrial and ribosomal DNA sequences to test the taxonomic validity of Clinostomum complanatum Rudolphi, 1814 in fish-eating birds and freshwater fishes in Mexico, with the description of a new species

Abstract: The taxonomic history and species composition of the genus Clinostomum has been unstable. Two species, Clinostomum complanatum Rudolphi, 1814 and Clinostomum marginatum Rudolphi, 1819, have been particularly problematic and its validity has been disputed for nearly 200 years. In this paper, we have made use of an integrative taxonomy approach, and we used, in first instance, DNA sequences of two genes (cox1 and ITS) to test the validity of C. complanatum, a species apparently widely distributed in Mexico and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 26 publications
6
71
0
Order By: Relevance
“…These digeneans are of significant commercial and ecological importance as parasites of ecologically threatened species of amphibians, as well as wild and farm-raised fish (Paperna, 1991). In North America, six named species have been reported (C. attenuatum, C. complanatum, C. heluans, C. intermedialis, C. marginatum and C. tataxumui) from avian, mollusc, fish and amphibian hosts (Bravo-Hollis, 1947;Stuart et al, 1972;McAllister, 1990;Sepúlveda et al, 1994Sepúlveda et al, , 1996Sepúlveda et al, , 1999Kinsella et al, 2004;Caffara et al, 2011;Sereno-Uribe et al, 2013). The larval stages of C. marginatum have been reported from hosts in commercial catfish ponds, marsh ramshorn snails Planorbella trivolvis (Say) and channel catfish Ictalurus punctatus (Rafinesque) (Lorio, 1989) collected from commercial catfish operations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These digeneans are of significant commercial and ecological importance as parasites of ecologically threatened species of amphibians, as well as wild and farm-raised fish (Paperna, 1991). In North America, six named species have been reported (C. attenuatum, C. complanatum, C. heluans, C. intermedialis, C. marginatum and C. tataxumui) from avian, mollusc, fish and amphibian hosts (Bravo-Hollis, 1947;Stuart et al, 1972;McAllister, 1990;Sepúlveda et al, 1994Sepúlveda et al, , 1996Sepúlveda et al, , 1999Kinsella et al, 2004;Caffara et al, 2011;Sereno-Uribe et al, 2013). The larval stages of C. marginatum have been reported from hosts in commercial catfish ponds, marsh ramshorn snails Planorbella trivolvis (Say) and channel catfish Ictalurus punctatus (Rafinesque) (Lorio, 1989) collected from commercial catfish operations.…”
Section: Discussionmentioning
confidence: 99%
“…Overstreet & Curran (2004) reported Clinostomum marginatum (Rudolphi, 1819) from herons, egrets and catfish obtained from production ponds in Louisiana and Mississippi, USA. In Mexico, C. complanatum has been found in great egrets (Violante-González et al, 2012); however recently Sereno-Uribe et al (2013) suggested that previous records of C. complanatum in Mexico are likely C. marginatum or the more recently recognized Clinostomum tataxumui Sereno-Uribe, PinachoPinacho, García-Varela & Pérez-Ponce de León, 2013 from great egret, great blue heron, and barethroated tiger heron Tigrisoma mexicanum Swainson. Furthermore, Caffara et al (2011) combined morphological and molecular data to differentiate adult and metacercaria stages of C. complanatum and C. marginatum and concluded that C. complanatum is the ''European'' species and is not present in the Americas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies, many of them having been published in JP, have revealed several cryptic species of trematodes (within the genera Clinostomum, Crassicutis, Oligogonotylus, Phyllodistomum) and acanthocephalans (Neoechinorhynchus, Pomphorhynchus) (Pe´rez-Ponce de Leo´n et al, 2008;Martı´nez-Aquino et al, 2009;Razo-Mendivil et al, 2010;Rosas-Valde´z et al, 2011;Garcı´a-Varela et al, 2012;SerenoUribe et al, 2013). Biogeographical studies are focused on unravelling relationships of the Mexican fauna of helminth parasites with that of the northern part of North America and Central America, and they search for general patterns and processes of formation of the parasite fauna (Vidal-Martı´nez and Kennedy, 2000;Aguilar-Aguilar et al, 2003; Pe´rez-Ponce de Choudhury, 2002, 2005; Pe´rez-Ponce de Leo´n et al, 2013).…”
Section: Geography Of Knowledgementioning
confidence: 99%
“…Also, this difference was associated with the different human activities existing among the studied areas, causing water quality differences 10 . It is well known that Clinostomum taxonomic history and species composition are unstable 12 . The confusing taxonomic history of the genus was reviewed by Gustinelli et al 6 and they reported between 13 and 27 valid species.…”
Section: Discussionmentioning
confidence: 99%